Análise do equilíbrio postural e desempenho de atividade de vida diária de indivíduos com doença pulmonar obstrutiva crônica: estudo transversal - Luiz, Rodrigo Pereira (2020)
Introduction: Chronic obstructive pulmonary disease (COPD) is characterized by airflow limitation associated with an inflammatory response and extrapulmonary manifestations, such as stress intolerance and physical inactivity. Objective: To analyze postural balance and the performance of daily life activity according to COPD and compare it with healthy adults. Methodology: Cross-sectional study, with participants of both sexes, diagnosed with COPD and healthy, were found to assess anthropometric data, lung function, dyspnea classification with the modified Medical Research Council (mMRC) questionnaire, health status with questionnaire CAT-COPD Assessment TEST, postural balance with the Berg balance scale, posturography with the Wii Balance Board® (WBB) platform, with open eyes (EO), eyes blindfolds (EB), eyes open on unstable ground (EOUG) and eyes blindfolded on unstable soil (EBUS), Glittre daily life activity performance. Results: 19 participants were included, 9 with COPD, for the GD group, 2 women and 7 men, with a mean age of 66.5 ± 6.4 years, and BMI 23.6 ± 3.7 kg / m², and 10 adults healthy, for the CG group, 5 women and 5 men, with a mean age of 62.8 ± 5.7 years, and BMI 27.2 ± 3.6 kg / m². On the Berg balance scale, the GD 54.0 ± 1.51 points and the CG 55.7 ± 0.48 points (p = 0.016), in the daily life activity test - Glittre, the DG 6.80 ± 2 , 96 minutes and the CG 3.79 ± 0.75 minutes (p = 0.016). In Posturography with WBB, in the area Ellipse in square centimeter, although the GD presents a larger area Ellipse in the conditions OY, OBY, OYUG, BYUS there was no difference, in length in centimeter and average speed in centimeter per second, the GD increased greater length and greater speed in all conditions, with a significant difference in all variables. There were correlations between posturography and BBS, ADL-Glittre and pulmonary function. Conclusion: Our data occur that there may be an alteration in postural balance by the Berg Balance scale and by posturography, under different conditions of vision and stability, as well as greater impairment of the performance of daily life activity by the AVD-Glittre test for disease attendance Chronic Obstructive Pulmonary Disease in relation to adult adults.